An optogenetic tool for the activation of endogenous diaphanous‐related formins induces thickening of stress fibers without an increase in contractility. Issue 7 (24th May 2013) - Rao, Megha Vaman; Chu, Pei‐Hsuan; Hahn, Klaus Michael; Zaidel‐Bar, Ronen
<x xml:space="preserve">Abstract</x> We have developed an optogenetic technique for the activation of diaphanous‐related formins. Our approach is based on fusion of the light‐oxygen‐voltage 2 domain of Avena sativa Phototrophin1 to an isolated Diaphanous Autoregulatory Domain from mDia1. This "caged" diaphanous auto‐regulatory domain was inactive in the dark but in the presence of blue light rapidly activated endogenous diaphanous‐related formins. Using an F‐actin reporter, we observed filopodia and lamellipodia formation as well as a steady increase in F‐actin along existing stress fibers, starting within minutes of photo‐activation. Interestingly, we did not observe the formation of new stress fibers. Remarkably, a 1.9‐fold increase in F‐actin was not paralleled by an increase in myosin II along stress fibers and the amount of tension generated by the fibers, as judged by focal adhesion size, appeared unchanged. Our results suggest a decoupling between F‐actin accumulation and contractility in stress fibers and demonstrate the utility of photoactivatable diaphanous autoregulatory domain for the study of diaphanous‐related formin function in cells. © 2013 Wiley Periodicals, Inc.